Accuracy and Challenges in the Vesical Imaging‐Reporting and Data System for Staging Bladder Cancer. Issue 2 (20th January 2022) - Meng, Xiaoyan; Hu, Henglong; Wang, Yanchun; Feng, Cui; Hu, Daoyu; Liu, Zheng; Kamel, Ihab R.; Li, Zhen
Abstract : Background: The Vesical Imaging‐Reporting and Data System (VI‐RADS) scoring system has been widely used to stage bladder cancer (BCa) since 2018. Purpose: To describe the characteristics of cases with discordant T2‐weighted imaging (T2WI) and diffusion‐weighted imaging (DWI) scores in patients with BCa and further verify the accuracy of the VI‐RADS scoring system and the necessity of dynamic contrast‐enhanced (DCE) sequence. Study Type: Retrospective. Subjects: A total of 106 patients (include 16.5% female) with bladder cancer. Sequence: T2WI (fast spin echo), DWI (echo planer imaging), and DCE (gradient echo). Assessment: Some cases are difficult to score according to the system, mainly when the T2WI (category 4) and DWI (category 2) sequence scores are discordant, termed the discordant group below. The complementary group will be termed concordant group. Each MRI sequence was reviewed respectively according to the 5‐point VI‐RADS scoring system by three observers. The diagnostic ability of sequences for evaluating muscle invasion by BCa was calculated using histopathology as the reference standards. Statistical Tests: Receiver operating characteristic (ROC) curve, DeLong test, intraclass correlation coefficient. A P value of 0.05 or less was considered statistically significant. Results: Fourteen cases (13.2%) had discordant VI‐RADS scoring system. In the discordant group, the area under the ROC curve (AUC) of DCE was 0.875, while the T2WI and DWI showed limited diagnostic performance (AUCs = 0.50). In the concordant group, there was no significant difference in diagnostic efficacy between the overall VI‐RADS (AUC: 0.950) and the combination of T2WI and DWI (AUC: 0.946) ( P  = 0.56). Among all patients, the AUC of overall VIRADS was 0.939 with a 3 or greater cutoff value. Data conclusion: The DCE was crucial in the discordant group for evaluating muscle‐invasiveness, while DCE may not be necessary for the concordant group. The VI‐RADS scoring system performed with overall good diagnostic performance in evaluating muscle‐invasiveness in BCa patients. Evidence Level: 4 Technical Efficacy: Stage 3